Outcomes of proximal fibular osteotomy in medial compartment knee osteoarthritis - Joshi, Kuldeep Mangal; Shrestha, S; Singh, Janith Lal; Serchan, Binod (Nepal Orthopaedic Association Journal, 2020)
INTRODUCTION: Medial compartment knee osteoarthritis is the commonest form of osteoarthritis (OA) of the knee. Although total knee arthroplasty (TKA) is the Gold Standard treatment in the management of severe OA, it is costly and requires expertise. Proximal fibular osteotomy (PFO) on the other hand is a simple, safe, fast and affordable surgery that does not require insertion of additional implants and possibly delay the degenerative process thereby buying time for eventual replacement surgery. The purpose of this study is to study the early outcomes of proximal fibular osteotomy in medial compartment knee osteoarthritis in terms of pain relief and improvement in joint dynamics. METHODS: This is a prospective observational study where 31 patients underwent the surgery and were followed-up with weight-bearing radiographs of the knee preoperatively and postoperatively to analyze the change in joint space dynamics. Knee pain was assessed using a visual analogue scale both pre-operatively and post-operatively. RESULTS: Significant improvement in knee pain was observed postoperatively. The mean Visual Analogue Scale score (VAS) after the surgery decreased to (2.60 ± 0.96) from ( 8.80 ± 1.17) (p-value < .05). Joint dynamics were also improved significantly with an increase in medial joint space from an average of (2.14 ± 0.50) preoperatively to (4.13 ± 0.67) (P-value < 0.05). Most patients exhibited improved walking capacity immediately after the surgery. CONCLUSION: PFO is an excellent, cost-effective, and safe surgery in relieving pain and improving joint function in patients with medial compartment arthritis of the knee provided the proper indications for surgery are met.